Concussion Incidence and Impact on Player Performance in Major League Baseball Players Before and After a Standardized Concussion Protocol. Issue 4 (14th April 2020) - Peterson, Joshua G.; Tjong, Vehniah K.; Terry, Michael A.; Saltzman, Matthew D.; Gryzlo, Stephen M.; Sheth, Ujash
Background: Sports-related concussions have garnered significant attention in recent years because of the negative effects they can have on a player's cognitive health and performance. In response to this growing concern, Major League Baseball (MLB) introduced a standardized concussion protocol during the 2011-2012 season. Purpose/Hypothesis: The purpose of this study was to compare the reported incidence of concussions and the subsequent performance of MLB players before and after the introduction of the standardized concussion protocol. We hypothesized that the introduction of the standardized concussion protocol would not have an impact on player performance postconcussion. Study Design: Cohort study; Level of evidence, 3. Methods: Players who suffered a concussion between 2001 and 2018 were identified from the MLB transactions page. Incidence and player performance were compared before and after the introduction of the standardized concussion protocol. Player performance was evaluated using traditional data and sabermetric data, which are advanced statistics used in conjunction with standard statistics to better compare players and teams. Player averages were calculated and compared using paired t tests for 30 days before and after concussion, 1 year before and after concussion, and career before and after concussion. Averages were also compared before and after the institution of the standardized concussion protocol using independent-measures t tests. Results: There were a total of 114 players who suffered 142 concussions, with 77% of those occurring after the introduction of the concussion protocol (32 before, 110 after). The average time missed because of concussion significantly decreased from 33.7 days (range, 10-122 days) to 18.9 days (range, 6-111 days) after the concussion protocol ( P = .0005). There was no difference in player performance (including batting average, on-base percentage, and slugging for batters; earned run average, fielding-independent pitching, and walks plus hits per inning pitched for pitchers) after concussion at any time point (30 days, 1 year, or career) when comparing these statistics before versus after the MLB concussion protocol. However, batter performance was significantly poorer 1 year after concussion and over the remainder of the players' careers ( P < .05). Conclusion: The number of reported concussions increased after the introduction of the MLB concussion protocol. However, players spent significantly less time on the disabled list without any adverse effect on player performance. Despite these changes, long-term batting performance was significantly poorer after concussion.